Germination of five Indonesian brown rice: evaluation of antioxidant, bioactive compounds, fatty acids and pasting properties - MUNARKO,Hadi (2022)
Abstract Germination can alter the physicochemical, nutritional, and nutraceutical value of brown rice. This study aimed to evaluate some characteristic changes from five Indonesian brown rice varieties during germination. The germination was carried out through a complete soaking method for up to 120 h, and the samples were taken and analyzed every 24 h. The results showed that germination increased GABA (γ-aminobutyric acid) content in brown rice. The highest level of GABA, up to 126.55 mg/100 g, obtained in rice var. Inpari 43, after 120 h. Germination also affected the changes in phenolic content, antioxidant capacity, and γ-oryzanol, while fatty acid compositions showed no changes. The pasting properties changed significantly after germination, especially in peak viscosity, final viscosity, breakdown, and setback. In conclusion, the changes in brown rice characteristics during germination, especially for increased GABA content and shifting of pasting properties, are valuable information for developing functional rice-based food products.